OVERPRESSURE CHARACTERIZATION IN SESULU FIELD, KUTAI BASIN - Made Agus Sutha Negara, I
Offshore Kutai Basin is one of the locations in Indonesia with overpressure zones, where most hydrocarbon discoveries are associated with this phenomenon. The research location, i.e., Sesulu Field, lies south of the Kutai Basin. Overpressure is indicated within the field. This study aims to analyse overpressure characteristics in the Sesulu Field using data from four wells (Wells SS-A1, SS-T1, SS-B1, and J1). The data consist of direct pressure measurements, wireline logs, temperature, mud weight, and vitrinite reflectance. The analysis reveals variation in the top of overpressure, ranging from 7100 ft TVDSS (Well SS-J1) to 9000 ft TVDSS (Well SS-B1). The variation may be controlled by lithology, particularly the ratio between permeable and impermeable rocks (net-to-gross ratio), which has implications on pressure transfer. A ‘pressure belly’ is observed in one of the wells in the study area, indicating pressure drainage and hydrodynamic flow within the reservoir. As a function of permeability, pressure may also control the thickness of the transition zone from low to high overpressure within the study area. The overpressure generating mechanism in each well can be well-analyzed based on wireline log responses (density, sonic, and resistivity). Generally, the high magnitude of overpressure in the study area is due to loading and unloading mechanisms as well as the combination of both.